2022
DOI: 10.1186/s12987-022-00365-5
|View full text |Cite
|
Sign up to set email alerts
|

Microglia-derived CCL2 has a prime role in neocortex neuroinflammation

Abstract: Background In myelin oligodendrocyte glycoprotein (MOG)-induced experimental autoimmune encephalomyelitis (EAE), several areas of demyelination are detectable in mouse cerebral cortex, where neuroinflammation events are associated with scarce inflammatory infiltrates and blood–brain barrier (BBB) impairment. In this condition, the administration of mesenchymal stem cells (MSCs) controls neuroinflammation, attenuating astrogliosis and promoting the acquisition of stem cell traits by astrocytes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 110 publications
0
9
0
Order By: Relevance
“…Maladaptive microglia and monocyte activation may also exert a detrimental effect on BBB function and integrity in COVID-19 ( 14 ). Interestingly, a recent publication has shown that microglia−derived chemokine MCP-1 (also known as CCL2) seems to have a major role in neocortex neuroinflammation and BBB disruption in a mouse model of autoimmune encephalomyelitis ( 48 ). Moreover, high blood MCP-1 levels have been associated with disease severity and mortality in COVID-19 ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…Maladaptive microglia and monocyte activation may also exert a detrimental effect on BBB function and integrity in COVID-19 ( 14 ). Interestingly, a recent publication has shown that microglia−derived chemokine MCP-1 (also known as CCL2) seems to have a major role in neocortex neuroinflammation and BBB disruption in a mouse model of autoimmune encephalomyelitis ( 48 ). Moreover, high blood MCP-1 levels have been associated with disease severity and mortality in COVID-19 ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…CCL2 is known to be up-regulated under various pathological conditions, including TBI, impairing the integrity of the blood–brain barrier (BBB) [47 , 48] . CCL2 also initiates an inflammatory response after brain injury through recruitment of microglia and macrophage to the area of injury [49 51] . Whether and how these processes interfere with the endogenous mechanism of BDNF function and neuroblasts migration need further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a recent study demonstrated the pivotal role of microglia in neocortex inflammation since they produce and secrete CCL2, a chemokine involved in immune cell recruitment and BBB-microvessel leakage. Notably, decreased MG-CCL2 expression was associated with a more restored BBB and diminished neuroinflammation ( 52 ). It is important to note that the immune status, referred to as polarization of microglia or macrophages, will be determined by the net effect of a variety of pro-inflammatory and anti-inflammatory stimuli, being the outcome of the response a balance between the strength of the detected signals.…”
Section: Microglial Cellsmentioning
confidence: 99%